How to prepare materials with a desired refraction coefficient? - Ramm, Alexander G. (American Institute of Physics, 2010)
In this talk a method is described fof 8f;Jfr tg materials with a desired refraction coefficient. The method consists of embedding into a material with known refraction coefficient many small particles of size a. The number of particles per unit vo ume around any point is prescribed, the distance between neighboring particles is O(a ) as a -+ 0, 0 < K. < 1 is a fixed para1neter. The total number of the embedded particle is O(a ). The physical properties of the particles are described by the boundary impedance ( of the m - th particle, ( = O(a ) as a -+ 0. The refraction coefficient is the coefficientn (x) in the wave equation ['v + k n (x)]u = 0.
Keywords: Mesarteritis; Refraction coefficient; Wave scattering; Small particles